Effectiveness and safety of pamidronate treatment in nonambulatory children with low bone mineral density - Myeongseob Lee; Ahreum Kwon; Kyungchul Song; Hae In Lee; Han Saem Choi; Junghwan Suh; Hyun Wook Chae; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2024)
Purpose Nonambulatory pediatric patients may have low bone mineral density (BMD) and increased risk of pathologic fractures. Though bisphosphonate therapy is the mainstream medical intervention in these children, clinical data regarding this treatment are limited. Therefore, this study aimed to evaluate the effectiveness and safety of bisphosphonate therapy in such children. Methods We conducted a retrospective study of 21 nonambulatory children (Gross Motor Function Classification System level V) with BMD z-score ≤ -2.0 who were treated with intravenous pamidronate for at least 1 year. These patients received pamidronate every 4 months at a dose of 1.0 to 3.0 mg/kg for each cycle and had regular follow-ups for at least 1 year. The main outcome measures were changes in BMD, risk rate of fracture, biochemical data, and adverse events. Results The average duration of pamidronate treatment was 2.0±0.9 years, and the mean cumulative dose of pamidronate according to body weight was 7.7±2.5 mg/kg/yr. After treatment, the mean lumbar spine bone mineral content, BMD, and height-for-age-z-score-adjusted BMD z-score (BMDhazZ) significantly improved. The relative risk of fracture after treatment was 0.21 (p=0.0032), suggesting that pamidronate treatment reduced fracture incidence significantly. The increase in the average dose per body weight in each cycle significantly increased the changes in BMDhazZ. Conclusions Pamidronate treatment improved the bone health of nonambulatory children with low bone density without any significant adverse events. Independent of cumulative dosage and duration of treatment, the effectiveness of pamidronate increased significantly with an increase in the average dose per body weight in subsequent cycles.